1998
DOI: 10.1097/00007890-199806150-00010
|View full text |Cite
|
Sign up to set email alerts
|

A Good Alternative to Reduce the Kidney Shortage

Abstract: Reducing the incidence of acute rejection and shortening ischemia time are conditions needed to guarantee a long graft survival of kidneys from NHB donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Renal function as evidenced by serum creatinine was quite good 2 years after transplantation. Only the high rate of delayed function stands out as an inferior outcome associated with the use of these kidneys, this outcome is similar to what has been reported elsewhere (1)(2)(3)(4)6).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Renal function as evidenced by serum creatinine was quite good 2 years after transplantation. Only the high rate of delayed function stands out as an inferior outcome associated with the use of these kidneys, this outcome is similar to what has been reported elsewhere (1)(2)(3)(4)6).…”
Section: Discussionsupporting
confidence: 89%
“…A number of investigators have reported excellent short-term outcomes using these donors (1)(2)(3)(4)(5)(6), and several different organ procurement organizations have demonstrated 10 -15% growth in organ donation as a result of the use of these donors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It includes the total number of patients, the number of studies used to evaluate each outcome, the summary statistic of OR or WMD, their calculated 95%CI, the P value, and a test of heterogeneity between the studies. Warm ischemia time was reported by seven studies (10,11,13,15,17,23,24) of 1280 patients. NHBD displayed a significantly longer WIT by 24 min (95% CI 20.43Ϫ27.80; PϽ0.001).…”
Section: Resultsmentioning
confidence: 97%
“…[20][21][22] The two previous groups that performed feasibility studies of LARB in the porcine model used either infusion of hypothermic saline into the renal artery or a bag of ice on the anterior kidney for hypothermia. [11][12][13] Although renal temperatures were not measured to confirm the efficacy of these measures, functional and histologic outcomes were favorable despite mean ischemia times of 49 or 61 minutes and times as long as 88 minutes (Table 3).…”
Section: Figmentioning
confidence: 99%